P2Y1 Purinergic Receptor Modulate Axon Initial Segment Initial Development - Zhang, Wei; Bonadiman, Angela; Ciorraga, María; Benitez, María José; Garrido, Juan José (Frontiers in Cellular Neuroscience, 2019)
Morphological and functional polarization of neurons depends on the generation and maintenance of the Axon Initial Segment (AIS). This axonal domain maintains axonal properties, but is also the place where the action potential (AP) is generated. All these functions require the AIS, a complex structure that is not fully understood. An integrated structure of voltage gated ion channels, specific cytoskeleton architecture, as well as, scaffold proteins contributes to these functions. Among them, ankyrinG plays a crucial role to maintain ion channels and membrane proteins. However, it is still elusive how the AIS performs its complex structural and functional regulation. Recent studies reveal that AIS is dynamically regulated in molecular composition, length and location in response to neuronal activity. Some mechanisms acting on AIS plasticity have been uncovered recently, including Ca2+, calpain or calmodulin mediated modulation, as well as post-translational modifications of cytoskeleton proteins and actin associated proteins. Neurons are able to respond to different kind of physiological and pathological stimuli from development to maturity by adapting their AIS composition, position and length. This raises the question of which are the neuronal receptors that contribute to the modulation of AIS plasticity. Previous studies have shown that purinergic receptor P2X7 activation is detrimental to AIS maintenance. During initial axonal elongation P2X7 is coordinated with P2Y1, another purinergic receptor that is essential for proper axon elongation. In this study, we focus on the role of P2Y1 receptor on AIS development and maintenance. Our results show that P2Y1 receptor activity and expression are necessary during AIS initial development, while has no role once AIS maturity is achieved. P2Y1 inhibition or suppression results in a decrease in ankyrinG, bIV-spectrin and voltage gated sodium channels accumulation that can be rescued by actin stabilization or the modulation of actin binding proteins at the AIS. Moreover, P2X7 or calpain inhibition also rescues ankyrinG decrease. Hence, a dynamic balance of P2Y1 and P2X7 receptors expression and function during AIS assembly and maturation may represent a fine regulatory mechanism in response to physiological or pathological extracellular purines concentration.